Redefining global strategy : crossing borders in a world where differences still matter - Ghemawat, Pankaj (Boston, Massachusetts : Harvard Business Review Press, 2018)
Why do so many global strategies fail--despite companies' powerful brands and other border-crossing advantages? Seduced by market size, the illusion of a borderless, "flat" world, and the allure of similarities, firms launch one-size-fits-all strategies. But cross-border differences are larger than we often assume, explains Pankaj Ghemawat in Redefining Global Strategy, with a New Introduction. Most economic activity--including direct investment, tourism, and communication--happens locally, not internationally. In this "semi-globalized" world, one-size-fits-all strategies don't stand a chance. Companies must instead reckon with cross-border differences. Ghemawat shows you how--by providing tools for: assessing the cultural, administrative, geographic, and economic differences between countries at the industry level and deciding which ones merit attention; tracking the implications of particular border-crossing moves for your company's ability to create value; and creating superior performance with strategies optimized for adaptation (adjusting to differences), aggregation (overcoming differences), and arbitrage (exploiting differences), and for compound objectives. In-depth examples reveal how companies such as Cemex, Toyota, Procter & Gamble, Tata Consultancy Services, IBM, and GE Healthcare have adroitly managed cross-border differences--as well as how other well-known companies have failed at this challenge. Crucial for any business competing across borders, this book will transform the way you approach global strategy.--
Part one. Value in a world of differences: Semiglobalization and strategy -- Differences across countries--The CAGE distance framework--Global value creation--The adding value scorecard--Part two. Strategies for global value creation: Adaptation--Adjusting to differences--Aggregation--Overcoming differences--Arbitrage--Exploiting differences--Playing the differences--The AAA triangle--Toward a better future--Getting started.
"With a new introduction"--Title page.
Includes bibliographical references and index.
BBS
Keywords: International business enterprises -- Management; Strategic planning; Intercultural communication; Business